Tackling inequalities : where are we now and what can be done? - Pantazis, Christina; Gordon, David, 1959- (Studies in poverty, inequality, and social exclusion., 2000)
This challenging book brings together contributions from leading poverty analysts on inequalities in income, wealth, standard of living, employment, education, housing, crime and health. It charts the extent of the growth in inequalities and offers a coherent critique of the New Labour government's policies aimed at those tackling this crisis.